The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1124/dmd.30.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Induction ofCYP3AExpression by Dehydroepiandrosterone: Involvement of the Pregnane X Receptor

Abstract: ABSTRACT:Dehydroepiandrosterone (DHEA) is a steroid produced by the human adrenal gland. Administration of pharmacological doses of DHEA to rats changes expression of many genes, including the cytochrome P450 family members CYP4A1 and CYP3A23. It is known that induction of CYP4A expression by DHEA requires the peroxisome proliferator-activated receptor ␣ (PPAR␣). In the current study, PPAR␣-null mice were used to examine the role of PPAR␣ in expression of CYP3A. In wild-type mice, 150 mg/kg DHEA-sulfate induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 31 publications
4
57
1
1
Order By: Relevance
“…Bruder et al (1997) suggested that DHEA might stimulate the oestrogen response element. Very recently, it was proposed that DHEA might activate the pregnane X receptor (Singleton et al 1999, Ripp et al 2002. A recent clinical study on the treatment of X-ALD patients with DHEA showed a lowering of long chain FAs but not of C24 FAs ( J Assies, E B Haverkort, R Lieverse & P Vreken, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Bruder et al (1997) suggested that DHEA might stimulate the oestrogen response element. Very recently, it was proposed that DHEA might activate the pregnane X receptor (Singleton et al 1999, Ripp et al 2002. A recent clinical study on the treatment of X-ALD patients with DHEA showed a lowering of long chain FAs but not of C24 FAs ( J Assies, E B Haverkort, R Lieverse & P Vreken, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…We observed the induction of P4503A23 in the livers of rats fed DHEA and, because DHEA is a pregnane derivative, it was likely that DHEA and its metabolites may act as a ligand of PXR (Ripp et al 2002). Using Pparα-null mice fed DHEA, we were unable to detect the induction of Cyp4a1, but there was a two-fold increase in the enzymatic activity and mRNA specific for Cyp3a11 in both wild-type and PPARα-null mice (Ripp et al 2002). In Pxr-null mice, we did not observe P4503A11 induction upon DHEA feeding (S J Webb and R A Prough, unpublished observations).…”
Section: Dhea Activation Of Pxrmentioning
confidence: 88%
“…In Pxr-null mice, we did not observe P4503A11 induction upon DHEA feeding (S J Webb and R A Prough, unpublished observations). Other experiments demonstrated that DHEA, Adiol, and Adione activate PXR in luciferase assays in HepG2 cells, using a vector containing two copies of the PXR responsive element (PXRE) from the rat Cyp3a23 gene (Ripp et al 2002). However, other oxidized metabolites of DHEA have no effect in stimulating PXRE-luciferase activity at low micromolar concentrations (Ripp et al 2002).…”
Section: Dhea Activation Of Pxrmentioning
confidence: 99%
See 2 more Smart Citations